MAKNA KERIS DAN PENGARUHNYA TERHADAP MASYARAKAT DI SURAKARTA - Arif Musadad, Akhmad (MIIPS, 2008)
This research aims to find out: the physical shape, development history, meaning and effect of keris.This research used ethnographic method, and it belonged to a case study. The population was the Surakartaâs society, while the sample is people considered as knowledgeable and who can be consulted with about the meaning and effect of keris. Technique of sampling used was purposive sampling. The data was collected using interview, observation, and literary study. The data analysis was conducted using interaction analysis, that is, through data collection, reduction, and conclusion drawing.From the result of research, it can be concluded that there are various types of keris, each of them having different name. Each keris is divided into several parts. In pakem it is mentioned about the keris luster, bringing good or bad effect into the owner. Keris had been known along time ago by Indonesian since they knew iron, and had been achieving the current progress since Majapahit time. Keris has a deep meaning for Javanese society. Because they believe that keris, particularly the one made in ancient time, has magical power. The keris, that is initially an arm, in its development has a complex function: as an arm, symbol, equipment, and art object. Keris affects various aspects of life, such as sosial-cultural, economical and faith.